Conspicuity of breast lesions at different b values on diffusion-weighted imaging - Chen, Xin; He, Xi-Jing; Jin, Rui; Guo, You-Min; Zhao, Xian; Kang, Hua-Feng; Mo, Li-Ping; Wu, Qian (BMC cancer, 2012)
Diffusion-weighted (DW) imaging has shown potential to differentiate between malignant and benign breast lesions. However, different b values have been used with varied sensitivity and specificity. This study aims to prospectively evaluate the influence of b value on the detection and assessment of breast lesions. Institutional review board approval and informed patient consent were obtained. Between February 2010 and September 2010, sixty women suspected of having breast cancer by clinical examination and mammography underwent bilateral breast MRI and DW imaging (with maximum b values of 600, 800, and 1000 s/mm(2)). Conspicuity grades of lesions at different b values on DW images were performed. Signal intensity and apparent diffusion coefficient (ADC) values were recorded and compared among different b values by the signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR) and receiver operating characteristic (ROC) curve. Fifty-seven lesions from 52 recruited patients including 39/57 (68%) malignant and 18/57 (32%) benign were confirmed with pathology. DCE MRI accurately detected 53 lesions with the sensitivity of 93.0% and specificity of 66.7%, and DW imaging accurately detected 51 lesions with the sensitivity of 89.5% and specificity of 100%. There were no significant differences in conspicuity grades compared among the three b values (P = 0.072), although the SNR and CNR of breast lesions decreased significantly with higher b values. Mean ADCs of malignant lesions (b = 600 s/mm(2), 1.07 ± 0.26 × 10-3 mm(2)/s; b = 800 s/mm(2), 0.96 ± 0.22 × 10-3 mm(2)/s; b = 1000 s/mm(2), 0.92 ± 0.26 × 10-3 mm(2)/s) were significantly lower than those of benign lesions (b = 600 s/mm(2), 1.55 ± 0.40 × 10-3 mm(2)/s; b = 800 s/mm(2), 1.43 ± 0.38 × 10-3 mm(2)/s; b = 1000 s/mm(2), 1.49 ± 0.38 × 10-3 mm(2)/s) with all P values <0.001, but there were no significant differences among the three b values (P = 0.303 and 0.840 for malignant and benign lesions, respectively). According to the area under the ROC curves, which were derived from ADC and differentiate malignant from benign lesions, no significant differences were found among the three b values (P = 0.743). DW imaging is a potential adjunct to conventional MRI in the differentiation between malignant and benign breast lesions. Varying the maximum b value from 600 to 1000 s/mm(2) does not influence the conspicuity of breast lesions on DW imaging at 1.5 T.